THE PHENOMENON OF «MASS CONSCIOUSNESS» IN E. FROMM'S PHILOSOPHY - Habriielian A. (World Science, 2019)
In this article, the author considered the concept of «Mass Consciousness» in the philosophy of Erich Fromm. The phenomenon of «Mass Consciousness» was studied from the standpoint of E. Fromm’s «Humanistic Radicalism», and was analyzed in comparison with classical Freudian psychoanalysis and other prominent thinkers of the twentieth century. It was found that according to Erich Fromm's social psychoanalysis, aggression is the result of social exclusion, mass consciousness, and conformism. The prevention of these phenomena can only be realized by a healthy humanistic society, in which faith, hope, love, understanding, sanity, mutual respect, empathy that cannot be explained by human instincts.